Altered Expression of Somatostatin Receptors in Pancreatic Islets from NOD Mice Cultured at Different Glucose Concentrations In Vitro and in Islets Transplanted to Diabetic NOD Mice In Vivo. (5th September 2011) - Ludvigsen, Eva; Stridsberg, Mats; Janson, Eva T.; Sandler, Stellan
Abstract : Somatostatin acts via five receptors (sst1-5 ). We investigated if the changes in pancreatic islet sst expression in diabetic NOD mice compared to normoglycemic mice are a consequence of hyperglycemia or the ongoing immune reaction in the pancreas. Pancreatic islets were isolated from NOD mice precultured for 5 days and further cultured for 3 days at high or low glucose before examined. Islets were also isolated from NOD mice and transplanted to normal or diabetic mice in a number not sufficient to cure hyperglycemia. After three days, the transplants were removed and stained for sst1-5 and islet hormones. Overall, changes in sst islet cell expression were more common in islets cultured in high glucose concentration in vitro as compared to the islet transplantation in vivo to diabetic mice. The beta and PP cells exhibited more frequent changes in sst expression, while the alpha and delta cells were relatively unaffected by the high glucose condition. Our findings suggest that the glucose level may alter sst expressed in islets cells; however, immune mechanisms may counteract such changes in islet sst expression.